The hydraulic characteristics of end-dump closure with the assistance of backwater-sill in diversion channel - 陆贺 胡志根 刘全 吕国轩 叶建群 任金明 (Journal of hydrodynamics. Series B, 2016)
The river closure is a key step in the water dam construction, and the end-dump closure is a general way to cut offthe river flow. The hydraulic characteristics at the closure gap are the main factors which affect the extent of closure difficulty. A method is proposed to reduce the difficulty of diversion channel closure by pre-building a closure structure called the backwater-sill at the downstream toe of the closure gap to change the flow pattern at the closure gap. The results of the physical model test and the three- dimensional numerical simulation indicate that the backwater-sill has the effects of raising the water level at the downstream toe of the closure gap, decreasing the water surface gradient, and reducing the closure drop and the flow velocity at the closure gap. The schemes with different dike widths, different closure gap widths, and different backwater-sill widths and heights are simulated. The results show that the height of the backwater-sill is the key factor affecting the hydro-indicators at the closure gap, while the influe- nce of the dike width, the closure gap width or the backwater-sill width can be ignored. The higher the backwater-sill is, the lower the hydro-indicators will be. Based on the numerical simulations and the physical model tests on the hydraulic characteristics at the closure gap of the backwater-sill assisted closure, the hydro-indicators and its calculation method are proposed to provide a theoreti- cal support for the river closure.